2007
DOI: 10.1111/j.1558-5646.2007.00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural Variation for a Hybrid Incompatibility Between Two Species of Mimulus

Abstract: Understanding the process by which hybrid incompatibility alleles become established in natural populations remains a major challenge to evolutionary biology. Previously, we discovered a two-locus Dobzhansky-Muller incompatibility that causes severe hybrid male sterility between two inbred lines of the incompletely isolated wildflower species, Mimulus guttatus and M. nasutus.An interspecific cross between these two inbred lines revealed that the M. guttatus (IM62) allele at hybrid male sterility 1 (hms1) acts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
131
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(137 citation statements)
references
References 54 publications
(99 reference statements)
4
131
1
1
Order By: Relevance
“…Vickery (1956Vickery ( , 1973Vickery ( , 1978 and Sweigart et al (2007) provided evidence that postzygotic isolation within and among populations of both species varied geographically, though biometrical line crosses were not used to determine the genetic basis. In one particular cross of two inbred lines, the main nuclear and mitochondrial loci underlying two forms of hybrid male sterility were mapped, and at least some of the alleles were shown to have restricted geographical distributions (Sweigart et al 2007;Case & Willis 2008). However, the extent to which this isolation varied across the geographical ranges of these largely sympatric species was unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vickery (1956Vickery ( , 1973Vickery ( , 1978 and Sweigart et al (2007) provided evidence that postzygotic isolation within and among populations of both species varied geographically, though biometrical line crosses were not used to determine the genetic basis. In one particular cross of two inbred lines, the main nuclear and mitochondrial loci underlying two forms of hybrid male sterility were mapped, and at least some of the alleles were shown to have restricted geographical distributions (Sweigart et al 2007;Case & Willis 2008). However, the extent to which this isolation varied across the geographical ranges of these largely sympatric species was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the nuclear incompatibility alleles involved are not polymorphic within species, but several considerations argue strongly against this. First, genetic mapping studies and laborious testcross analysis of the two major loci, hms1 and hms2, underlying hybrid sterility in the Oregon IM Â SF cross revealed that, while the M. nasutus hms2 incompatibility allele appears fixed within that species, the M. guttatus hms1 incompatibility allele is geographically localized at intermediate frequencies only in the IM population (Sweigart et al 2007). At least some of the individuals that we sampled from that population probably lacked that allele, since we did not observe complete sterility in any F 2 s in the cross with the M. nasutus SF population (Sweigart et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, hybrid incompatibilities may vary across geography, such that selection against hybridization is stronger in some regions or acts at different life history stages across areas (Parris, 2001; Sætre, Kr.l, M., Bureš, S., & Ims, R. A. 1999; Sweigart, Mason, & Willis, 2007; Veen et al., 2001). In chorus frogs, even males derived from the same population vary substantially in levels of hybrid sterility, lending support for this hypothesis (Lemmon & Lemmon, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…But intraspecific polymorphisms for hybrid sterility factors are not restricted to highly selfing species. One such factor causing hybrid male sterility in crosses between the outcrossing Mimulus guttatus and the selfing M. nasutus was found to be polymorphic in the outcrossing M. guttatus and to be strongly geographically restricted (Sweigart et al, 2007).…”
Section: Evolution Of Postzygotic Barriersmentioning
confidence: 99%